ISLAM DAN DEMOKRASI (Telaah Pemikiran Politik M. Husein Haikal) - Nunung Susfita (Universitas Islam Negeri (UIN) Mataram, 2015)
Religion and democratization resurgence was the most important phenomena in the latest decade of 20 th century. Various regions in the world, religious resurgence movements run well and sometimes reinforce political system formation which is more democratic. Islamic politics is often seen as fusion between religionandpolitics. In modern term, Islam is religion and state (??????? ?? ???), in group of Islamic thinkers or non-Islam, they state that Islam is comprehensive way of life and know the clergy or formal institution. There were some political systems which were applied in Islamic world in the beginning of modern era. Some were big kingdoms, such as Usmaniyah Sultanate in Europe and Middle East and Mughol Sultanate in India, governed by Sultan. Islamic role in politics started changing significantly in 1970s. Instead of reactive element of political community, Islamic group could step forward as initiative resource for political development and change. Islamic organizations were important part of Islamic resurgence in the latest decade of 20 th century. They not only were busy to response initiative of other sides but also represented the beginning of alternative politic-social orientation which was able to be trusted. This movement reflected multiple aspirations from modern educated professional group and Islamic society that wanted to participate bigger in political process and to realize the more Islamic society. Therefore, these new organizations were success to join two main inclinations in the end of 20 th century, namely: “religious and democratic resurgence”.